Anticoagulation strategies for pediatric continuous renal replacement therapy - Aakash Chandran Chidambaram; Ankit Mangla; Karthi Nallasamy (Journal of Pediatric Critical Care)
Continuous renal replacement therapy (CRRT) in children is quite challenging to manage because of their increased propensity for circuit clotting. The anticoagulant strategies are paramount in reducing the downtime in pediatric CRRT. The most commonly used anticoagulants in pediatrics are unfractionated heparin and citrate anticoagulation. The other less explored options include regional heparin protamine anticoagulation, prostacyclin, low-molecular-weight heparin, and thrombin antagonists. The choice of anticoagulant primarily depends on the patient’s condition, availability and cost of the anticoagulant, potential side effects, and the local expertise for troubleshooting. This article aims to bring about the merits and demerits of the different anticoagulants available for CRRT and the available evidence for the use of each of these anticoagulants.